PERAN GURU PENGGERAK DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SD NEGERI SE-KECAMATAN MOYO UTARA KABUPATEN SUMBAWA NUSA TENGGARA BARAT - Ramdani, Nadila; Hardiansyah, Hardiansyah; Najwa, Lu’luin (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The quality of learning in elementary schools located in remote areas such as North Moyo District still faces various challenges, particularly limited facilities, restricted access, and the insufficient capacity of teachers to manage effective instruction. These conditions require the presence of Driving Teachers (Guru penggerak) as learning leaders capable of initiating meaningful changes in school practices. This study aims to explain the role of Driving Teachers in improving reciprocal learning, the strategies they employ, as well as the supporting and inhibiting factors encountered during implementation. A qualitative descriptive method with a case study approach was used, involving five public elementary schools through observation, interviews, and documentation. The findings indicate that Driving Teachers enhance learning quality through instructional leadership, the application of interactive and differentiated learning methods, and the development of a reflective culture among teachers. Key strategies include establishing learning communities, collaborating with stakeholders, and implementing contextual learning based on local potential. These findings highlight the need for a more systematic support system to replicate the innovative practices of Driving Teachers and strengthen the collaborative school ecosystem to improve learning quality sustainably. ABSTRAK Mutu pembelajaran di sekolah dasar di wilayah terpencil seperti Kecamatan Moyo Utara masih menghadapi berbagai tantangan, terutama terkait keterbatasan sarana, akses, serta kapasitas guru dalam mengelola pembelajaran yang efektif. Kondisi tersebut menuntut hadirnya guru penggerak sebagai pemimpin pembelajaran yang mampu menginisiasi perubahan praktik mengajar di sekolah. Penelitian ini bertujuan menjelaskan peran guru penggerak dalam meningkatkan pembelajaran timbal balik, strategi yang digunakan, serta faktor pendukung dan penghambat yang ditemukan dalam proses pelaksanaannya. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus pada lima SD Negeri melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru penggerak memperkuat mutu pembelajaran melalui kepemimpinan instruksional, penerapan metode belajar interaktif, diferensiasi, serta pengembangan budaya reflektif di kalangan guru. Strategi utama meliputi pembentukan komunitas belajar, kolaborasi dengan pemangku kepentingan, dan penerapan pembelajaran kontekstual berbasis potensi lokal. Temuan ini menegaskan perlunya dukungan sistem yang lebih sistematis agar praktik inovatif guru penggerak dapat direplikasi dan memperkuat ekosistem kolaboratif sekolah untuk meningkatkan mutu pembelajaran secara berkelanjutan.